Effect of Airfoil Concavity on Wind Turbine Blade Performances - Jianlong Ma; Yafan Duan; Ming Zhao; Wenchun Lv; Jianwen Wang; Qilao Meng Ke; Yongfeng Ren (Shock and Vibration)
Although the optimization of wind turbine blade aerodynamic performance has achieved fruitful results, whether airfoil concavity, an important method for preventing flow separation, is also feasible for improving the aerodynamic performance has not been confirmed scientifically. Thus, we selected the blade of a small horizontal-axis wind turbine as a research model and proposed an optimization method based on airfoil concavity near the trailing edge of the blade suction surface. The experimental results showed that airfoil concavity improved blade aerodynamic performance by 3–15%. Subsequently, its effects on the sound pressure level within the wake flow field were investigated using an acoustic array, and the results suggested that the sound pressure level was reduced by 9.6–15.8%. Lastly, a modal test of the rotor blade was conducted. Although the natural frequencies of the 1st and 2nd order vibrations had hardly changed, their vibrational stiffness were increased by 7 and 4.9%, respectively, which indicated that airfoil concavity significantly improved structural robustness.